The Urgency of Artificial Intellengence-Based Learning in Enhancing Local Wisdom in The Era Of Society 5.0 - Hosna, Rofiatul; Nurhidayati, Titin; Sain, Zohaib Hassan (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Artificial Intelligence (AI)-based learning has the potential to transform education in the Society 5.0 era by offering a more personalized and adaptive approach to teaching and learning. This has both positive and negative impacts. Among the negative impacts of progress are moral decadence and the decline of cultural values. Solutions are needed to address this by integrating local wisdom into learning. Furthermore, local wisdom must also coexist with technological advances in the era of society 5.0, namely artificial intelligence. This study aims to explore the urgency of artificial intellengence-based learning in enhancing local wisdom in the era of society 5.0. This study employed qualitative methods. Data collection was conducted through a literature review. The data collected came from several books, scientific journals and articles relevant to the research objectives. The results of this study show that artificial intelligence-based learning can enhance local wisdom in the era of Society 5.0 and has great potential to increase the effectiveness of the learning process, as teachers are able to integrate local wisdom-based content into their learning. Conclusion, an artificial intelligence-based learning can enhance local wisdom in the era of Society 5.0 and can be a solution to fortify students from moral decadence while still keeping up with the increasingly rapid advances in science and technology.